2011
DOI: 10.1186/1471-2164-12-459
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of immune responses to cardiomyopathy syndrome (CMS) in Atlantic salmon

Abstract: BackgroundCardiomyopathy syndrome (CMS) is a disease associated with severe myocarditis primarily in adult farmed Atlantic salmon (Salmo salar L.), caused by a double-stranded RNA virus named piscine myocarditis virus (PMCV) with structural similarities to the Totiviridae family. Here we present the first characterisation of host immune responses to CMS assessed by microarray transcriptome profiling.ResultsUnvaccinated farmed Atlantic salmon post-smolts were infected by intraperitoneal injection of PMCV and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
89
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(110 citation statements)
references
References 51 publications
21
89
0
Order By: Relevance
“…In addition, there were correlations between the expression of genes related with immune responses, viral load and heart lesions, in agreement with Timmerhaus et al [10]. Importantly, however, the temporal differences observed between the different dietary treatments in the present study strengthened these correlations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, there were correlations between the expression of genes related with immune responses, viral load and heart lesions, in agreement with Timmerhaus et al [10]. Importantly, however, the temporal differences observed between the different dietary treatments in the present study strengthened these correlations.…”
Section: Discussionsupporting
confidence: 93%
“…The time-courses for the development and resolution of histopathology and immune gene responses were similar to those observed previously [10, 11]. In addition, there were correlations between the expression of genes related with immune responses, viral load and heart lesions, in agreement with Timmerhaus et al [10].…”
Section: Discussionsupporting
confidence: 89%
“…These findings were pointing the high cell turn over in the hearts where DNA damage/repair might be the case (as identified by PCNA, caspase 3 and TUNEL reactivity) (Table 2) (Ferguson et al, 1986;Poppe and Ferguson, 2006;Kongtorp et al, 2004Kongtorp et al, , 2006. In addition, the transcriptomic profile of CMS-affected fish has shown the upregulation of apoptosis genes, supporting the strong to moderate levels of apoptosis staining in diseased hearts (Timmerhaus et al, 2011).…”
Section: Disease Outbreaks Involving Cardiac Manifestations Have Incrmentioning
confidence: 73%
“…The common regulatory mechanisms have been suggested for the expression of MHC class I and II in Atlantic salmon (Koppang et al, 1999). Recently, a CMS transcriptomic study identified the up-regulation of T-lymphocytes (CD3 and CD8), MHC and apoptotic genes, and also correlated with histopathological changes (Timmerhaus et al, 2011). The increased presence of MHC class II + cells have been described in granulomatous uveitis and amoebic gill disease of Atlantic salmon (Koppang et al, 2004;Morrison et al, 2006).…”
Section: Disease Outbreaks Involving Cardiac Manifestations Have Incrmentioning
confidence: 97%
“…Later years have shown a breakthrough in establishing the etiology of CMS: in 2009, 2 studies were published independently, both reporting successful experimental transmission of CMS in Atlantic salmon using tissue homogenates from fish collected during outbreaks of CMS in the field (Bruno & Noguera 2009, Fritsvold et al 2009). Subsequently, additional challenges have been performed where homogenates were filtered through 0.22 μm filters before successfully transmitting CMS to healthy fish, indicating that the infectious agent is a virus (Timmerhaus et al 2011). In 2010, a major breakthrough was achieved when 2 independent research groups both identified the causal agent for CMS, a hitherto unknown virus belonging to the family Totiviridae, which was subsequently named piscine myocarditis virus (PMCV).…”
Section: Introductionmentioning
confidence: 99%